Synthesis, Characterization, Catalytic Activity, and DFT Calculations of Zn(II) Hydrazone Complexes - Adejumo, Temiloluwa T. (Molecules, 2020)
Two new Zn(II) complexes with tridentate hydrazone-based ligands (condensation products of 2-acetylthiazole) were synthesized and characterized by infrared (IR) and nuclear magnetic resonance (NMR) spectroscopy and single crystal X-ray diffraction methods. The complexes 1, 2 and recently synthesized [ZnL(3)(NCS)(2)] (L(3) = (E)-N,N,N-trimethyl-2-oxo-2-(2-(1-(pyridin-2-yl)ethylidene)hydrazinyl)ethan-1-aminium) complex 3 were tested as potential catalysts for the ketone-amine-alkyne (KA(2)) coupling reaction. The gas-phase geometry optimization of newly synthesized and characterized Zn(II) complexes has been computed at the density functional theory (DFT)/B3LYP/6–31G level of theory, while the highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO and LUMO) energies were calculated within the time-dependent density functional theory (TD-DFT) at B3LYP/6-31G and B3LYP/6-311G(d,p) levels of theory. From the energies of frontier molecular orbitals (HOMO–LUMO), the reactivity descriptors, such as chemical potential (μ), hardness (η), softness (S), electronegativity (χ) and electrophilicity index (ω) have been calculated. The energetic behavior of the investigated compounds (1 and 2) has been examined in gas phase and solvent media using the polarizable continuum model. For comparison reasons, the same calculations have been performed for recently synthesized [ZnL(3)(NCS)(2)] complex 3. DFT results show that compound 1 has the smaller frontier orbital gap so, it is more polarizable and is associated with a higher chemical reactivity, low kinetic stability and is termed as soft molecule.